Physical fitness and anthropometric correlates of 500 m rowing performance in Indonesian athletes - Asmuddin; Sabrin, La Ode Maklum; Ilahi, Bogy Restu; Pranata, Doni; Amran (UIR Press, 2025)
Background: Rowing performance is shaped by athletes’ physical fitness and anthropometric characteristics, yet evidence from Indonesian rowing populations remains scarce. This gap is critical as declining performance in Kendari highlights the need to identify key predictors of 500 m rowing performance to inform more targeted, evidence-based training programs. Objectives: This study aimed to examine the relationship between physical ability, anthropometric characteristics, and 500 m rowing performance among male national rowing athletes at PPLP Kendari. Methods: A correlational quantitative design with a cross-sectional approach was employed. Thirty-nine male athletes aged 15-25 years were purposively selected from a total population of 60 based on inclusion criteria, including active participation in centralized training for at least six months, injury-free status, and official registration during the 2024 training season. Data were collected using standardized anthropometric and physical ability tests. Statistical analyses were conducted using descriptive statistics and multiple regression, with model assumptions confirmed (Kolmogorov-Smirnov, p > 0.05; VIF = 1.12; condition index = 8.5). Findings/Results: The regression analysis revealed a significant model (F(2,36) = 6.619, p = 0.004), explaining 51.9% of the variance in 500 m rowing performance (R2 = 0.519, SEE = 4.4 s). Anthropometric variables contributed 17.7% (R2 = 0.177) and physical ability variables 16.2% (R2 = 0.162), indicating that the combined model provided stronger explanatory power. Conclusion: Both anthropometric and physical ability factors demonstrated a moderate positive correlation with rowing performance. The findings emphasize the combined influence of physique and conditioning in achieving optimal rowing outcomes. This study contributes empirical evidence on the determinants of rowing success among Indonesian athletes and offers practical insights for designing targeted and evidence-based training programs.